Perlindungan Terhadap Paten Asing Berdasarkan Sistem Hukum Paten di Indonesia Pasca TRIPs-WTO - Kurniawan - (Jatiswara, 2012)
The establishment of Law number 14 of 2001 concerning Patent as a follow up policy after the ratification of the World Trade Organization (WTO) including its attachment concerning Trade Related Intellectual Property Rights (TRIPs) has brought legal consequence. That is to apply The TRIPs agreement in national law where one of the principle is knows as the National principle toward foreign patents in Indonesia. The foreign Patent rights will be preserved as long as the invention has registered to directorate-general of Intellectual Property Rights of the Republic of Indonesia. The invention registration could be applied in 2 (two) mechanism i.e. priority right registration and Patent Cooperation Treaty (PCT) and the application must be authorized by Indonesian IPR consultant.